PENGAMBILAN KEPUTUSAN INVESTASI MANAJEMEN WAKTU UNTUK LEBIH TERENCANA BAGI WARGA DI KECAMATAN KOTA GAJAH - Listyaningsih, Erna; Nurbaiti, Nurbaiti; Mufahamah, Euis; Muhammad, Muhammad; Indriani, Wiewiek (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2022)
The success or failure of every thing we do is often caused by the maximum or not optimal plan that has been carried out and how much time we sacrifice for the success of the plan. Not only investing in the form of money, but making the right decisions in using the best possible time will make life more planned through time management.Time management is done to manage or plan one's life goals or aspirations from the beginning until the goal is achieved. This service provides knowledge about how to manage time as effectively and efficiently as possible so that the time used can be used for better purposes. This service is carried out in Kotagajah sub-district, Central Lampung. The method used is to present the material through presentations. The achievement of this goal is that the general public, youth youth organizations and Women Farmer Groups in the Kotagajah sub-district have become even more productive in utilizing their time especially in using it for business purposes.